Literature as Social Critique: Examining Moral Discourse and Collective Consciousness in Fictional Narratives - Abdurahman, Abdurahman; Qudah, Nasser; Gittens, Leon (Yayasan Adra Karima Hubbi, 2026)
Background. Fictional narratives have long functioned as a medium of social critique, articulating moral discourse and shaping collective consciousness within changing social contexts. In contemporary societies marked by ethical uncertainty, ideological polarization, and social transformation, literature increasingly engages with questions of moral responsibility, social values, and communal identity, positioning fiction as a reflective and critical social practice. Purpose. This study aims to examine how fictional narratives construct moral discourse and contribute to the formation of collective consciousness, highlighting literature’s role in critiquing social norms and ethical frameworks. Method. The study employs a qualitative interpretative approach through thematic and narrative analysis, drawing on moral philosophy and cultural theory. Selected fictional texts from diverse sociocultural contexts are analyzed using close reading to identify moral themes, narrative strategies, and representations of collective values. Results. The findings reveal that fictional narratives articulate moral discourse through character dilemmas, symbolic conflicts, and narrative judgment, enabling readers to engage critically with social norms. Literature fosters collective consciousness by transforming individual moral struggles into shared ethical reflection, thereby linking personal experience with broader social concerns. Conclusion. This study concludes that fiction functions as an influential form of social critique by mediating moral discourse and cultivating collective consciousness, affirming literature’s enduring relevance in ethical and social inquiry.